Evolutionary history and eco‐climatic diversification in southern African dung beetle Sisyphus. (4th October 2020) - Daniel, Gimo M.; Davis, Adrian L. V.; Sole, Catherine L.; Scholtz, Clarke H.
Abstract: Aim: The high diversity of species in southern Africa has been attributed to geological and palaeoclimatic factors. The timing of radiations in some groups is held to be linked to these geoclimatic trends. Using the Scarabaeinae dung beetle genus, Sisyphus, as a model system, we investigate how geological uplift and climatic changes in the late Cenozoic affected its diversification patterns in southern Africa. Location: Southern Africa. Taxon: The dung beetle genus, Sisyphus Latreille, 1807 (Coleoptera: Scarabaeidae: Scarabaeinae). Methods: A dated molecular phylogeny of southern African Sisyphus was compared with a factor analysis of species distribution data that statistically defined groups of species according to current climatic distribution. We used these climatic clusters to estimate ancestral ranges using the "BioGeoBEARS" R package. A lineage through time plot was calculated using the R package 'APE'. We used Bayesian diversification models (compound Poisson process on mass extinction times) to test hypotheses on how late Cenozoic uplift and climatic changes affected speciation and extinction of Sisyphus . Furthermore, we implemented ecological niche modelling in MaxEnt to predict the habitat suitability of species under present climatic conditions. Results: Four species groups defined from factor analysis of current climatic distribution data are primarily restricted to the moist summer rainfall region in the northeast. Species diversification occurred from the mid‐Miocene until the Pleistocene, during which the central southern African plateau was uplifted in tandem with the advent of winter rainfall and arid climatic zones to the southwest. The ancestor of Sisyphus was centred in eastern low to mid‐altitude areas. Speciation rates were higher in the Miocene to Pliocene, followed by a dramatic drop during the transition to the Pleistocene. Main conclusions: The taxonomic and eco‐climatic diversification of sisyphines is coincident with geological uplift and changes in climate in east‐central southern Africa. However, phylogenetic relationships of southern African Sisyphus species are not homogenously distributed with respect to geography and climate.